The influence of a Mediterranean Diet with and without Red Wine on the Haemostatic and Inflammatory Parameters of Subjects with the Metabolic Syndrome - Mansvelt, E.P.G.; Fourie, E.; Blackhurst, D.; Kotze, T.; Stofberg, H.; van der Merwe, S.; Kotze, M.J.; van Velden, D.P. (South African Journal of Enology and Viticulture, 2016)
This 8 week study examined whether a Mediterranean diet supplemented with red wine, had an acute impact on subjects diagnosed with the metabolic syndrome. Twelve non-smoking subjects with diagnostic criteria of the metabolic syndrome on minimal medication, consumed a Mediterranean-like diet for 4 weeks respectively without and with red wine. The amount of red wine consumed was 250 ml (26 grams of alcohol) per day for male and 180 ml (19 grams) per day for female participants. A nutrigenetic profile for cardiovascular risk factors was performed on each participant. Fasting blood specimens were taken at baseline, after the diet and after the diet with wine interventions for platelet function, procoagulants FVII and FVIII, von Willebrand’s factor, fibrinogen, tissue plasminogen activator, plasminogen activator inhibitor-1, highly sensitive C-reactive protein and oxygen radical absorbance capacity (ORAC). After both periods of diet without wine and with wine, ORAC increased significantly compared to baseline levels. Except for platelet H2O2 fluxes and FVII concentration, none of the haemostatic or inflammatory parameters changed significantly after the intervention periods compared with baseline levels. Genetic risk factors for cardiovascular disease were identified in all study participants and the potential genotypic effects relevant to this study were generally in agreement with expected phenotypic response following the dietary intervention. Our conclusions are that the period of intervention was too short for substantial changes in haemostatic or in inflammatory parameters in subjects who already manifest some changes in their cardiovascular system and who showed diverse genetic profiles underlying increased cardiovascular risk.